Research priorities for expanding access to methadone treatment for opioid use disorder in the United States: A National Institute on Drug Abuse Clinical Trials Network Task Force report. Issue 3 (3rd July 2021) - Joudrey, Paul J.; Bart, Gavin; Brooner, Robert K.; Brown, Lawrence; Dickson-Gomez, Julie; Gordon, Adam; Kawasaki, Sarah S.; Liebschutz, Jane M.; Nunes, Edward; McCarty, Dennis; Schwartz, Robert P.; Szapocnik, José; et al.
Abstract: In the US, methadone treatment can only be provided to patients with opioid use disorder (OUD) through federal and state-regulated opioid treatment programs (OTPs). There is a shortage of OTPs, and racial and geographic inequities exist in access to methadone treatment. The National Institute on Drug Abuse Clinical Trials Network convened the Methadone Access Research Task Force to develop a research agenda to expand and create more equitable access to methadone treatment for OUD. This research agenda included mechanisms that are available within and outside the current regulations. The task force identified 6 areas where research is needed: (1) access to methadone in general medical and other outpatient settings; (2) the impact of methadone treatment setting on patient outcomes; (3) impact of treatment structure on outcomes in patients receiving methadone; (4) comparative effectiveness of different medications to treat OUD; (5) optimal educational and support structure for provision of methadone by medical providers; and (6) benefits and harms of expanded methadone access. In addition to outlining these research priorities, the task force identified important cross-cutting issues, including the impact of patient characteristics, treatment, and treatment system characteristics such as methadone formulation and dose, concurrent behavioral treatment, frequency of dispensing, urine or oral fluid testing, and methods of measuring clinical outcomes. Together, the research priorities and cross-cutting issues represent a compelling research agenda to expand access to methadone in the US.